2016
DOI: 10.1177/1066896916665203
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Bone Marrow Involvement in Intravascular Large B-Cell Lymphoma

Abstract: Intravascular large B-cell lymphoma (IVLBCL) is a rare subtype of diffuse large B-cell lymphoma. Thirteen cases of IVLBCL with a median age of 56 years were analyzed retrospectively. Nonspecific symptoms such as fever and hepatosplenomegaly were the most common manifestations, and the bone marrow was usually involved in 8/13 (61.5%) cases. All tumors expressed CD20, and 12/13 (92.3%) of the tumors exhibited a nongerminal center phenotype by Hans algorithm. CD5 was expressed in 3/12 (25%) of the tumors. MYC was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…In agreement with previous reports [6,18,23,24], we found comparable age at diagnosis (67 years old) but slightly older than other Asians [4,11,20]. A slight male predominance which is consistent with studies from Thailand [11,20], Taiwan [4], and China [22] was observed in our study, although studies by Murase et al [24] and Rajyaguru et al [21] showed no gender preference. Fever was found in the majority of patients while neurologic abnormalities were also relatively common in this study.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous reports [6,18,23,24], we found comparable age at diagnosis (67 years old) but slightly older than other Asians [4,11,20]. A slight male predominance which is consistent with studies from Thailand [11,20], Taiwan [4], and China [22] was observed in our study, although studies by Murase et al [24] and Rajyaguru et al [21] showed no gender preference. Fever was found in the majority of patients while neurologic abnormalities were also relatively common in this study.…”
supporting
confidence: 93%
“…Our results confirmed the variable morphology of cutaneous manifestations as seen in other studies [2]. Regarding bone marrow study, although a recent series of IVLBCL patients diagnosed by random skin biopsy showed no BM involvement [11], we found approximately 35% with BM infiltration which is consistent with previous studies ranging from 26.7% to 100% [4,6,20,22,24,26,27]. Additionally, we found that increased sera LDH and ferritin were exceedingly common in IVLBCL patients, consistent with earlier publications reporting 75%-100% of elevated LDH [5,11,20,22,23,26] and 80-100% of elevated ferritin [4,26] in IVLBCL patients.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Unlike other lymphomas of the CNS, 14 , 16 BBB-penetrating drugs, such as MTX and cytarabine, are rarely included in chemotherapy regimens for CNS-involved IVLBCL. As the number of patients treated with BBB-penetrating drugs was small, our analysis failed to reach a definitive conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…of IVLBCL in a bone marrow biopsy. 8 In our case, however, bone marrow biopsy results were negative.…”
mentioning
confidence: 72%